2013
DOI: 10.1093/ndt/gft015
|View full text |Cite
|
Sign up to set email alerts
|

How acute kidney injury is investigated and managed in UK intensive care units--a survey of current practice

Abstract: Considerable variation exists in the investigation and management of AKI in UK ICUs. Despite increasing recognition of the importance of AKI, few ICUs are aware of RIFLE and AKIN criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 21 publications
1
36
0
6
Order By: Relevance
“…For example, in the DOREMI study, a multicenter observational study conducted mainly in Italy from 2005 to 2007, the median CRRT dose was 34.3 mL kg -1 h -1 [11]. Another survey conducted in the UK in 2009 and 2010 revealed that the most common standard dose of CVVH prescribed in ICUs was 35 mL kg -1 h -1 [12]. In an international survey for RRT in the ICU, in which 80% of respondents were from Europe, the average ultrafiltration dose was 35 mL kg -1 h -1 , while for septic patients it was also 35 mL kg -1 h -1 [13].…”
Section: Movement To Higher Crrt Hemofiltration Ratementioning
confidence: 99%
“…For example, in the DOREMI study, a multicenter observational study conducted mainly in Italy from 2005 to 2007, the median CRRT dose was 34.3 mL kg -1 h -1 [11]. Another survey conducted in the UK in 2009 and 2010 revealed that the most common standard dose of CVVH prescribed in ICUs was 35 mL kg -1 h -1 [12]. In an international survey for RRT in the ICU, in which 80% of respondents were from Europe, the average ultrafiltration dose was 35 mL kg -1 h -1 , while for septic patients it was also 35 mL kg -1 h -1 [13].…”
Section: Movement To Higher Crrt Hemofiltration Ratementioning
confidence: 99%
“…The two most commonly used techniques lie at opposite ends of the spectra [11]. Peritoneal dialysis (PD) is rarely used to treat AKI in developed countries where extracorporeal RRT methods are widely available, but is sometimes used in children and occasionally in adults where there are significant problems with vascular access or haemodynamic stability.…”
Section: Renal Replacement Therapy In Akimentioning
confidence: 99%
“…Plusieurs recommandations d'experts et expériences d'équipes s'accordent pour dire que la gestion des séances d'EER par un personnel formé et fondée sur des procédures est nécessaire [168,169,[173][174][175][176][177]. Dans une enquête récente sur la prise en charge de l'IRA menée dans 188 réanimations au Royaume-Uni, 73 % des services déclaraient, effectivement, disposer d'une procé-dure standardisée pour la réalisation de l'EER [178]. Les risques infectieux liés à la pratique de l'EER sont multiples.…”
Section: Les éQuipes Médicales Et Paramédicales Doivent êTre Forméesunclassified